Assessment of body force effects in flow condensation, part II: Criteria for negating influence of gravity. (March 2017) - O'Neill, Lucas E.; Park, Ilchung; Kharangate, Chirag R.; Devahdhanush, V.S.; Ganesan, V.; Mudawar, Issam
Highlights: This study concerns development of criteria to achieve gravity independent flow condensation. Criteria developed by comparing data for horizontal flow, upflow and downflow. Two criteria developed, one to negate gravity effects parallel to and second perpendicular to flow direction. Use of separated flow model provides high accuracy in determining the two criteria. Abstract: This study concerns the development of a set of mechanistic criteria capable of predicting the flow conditions for which gravity independent flow condensation heat transfer can be achieved. Using FC-72 as working fluid, a control-volume based annular flow model is solved numerically to provide information regarding the magnitude of different forces acting on the liquid film and identify which forces are dominant for different flow conditions. Separating the influence of body force into two components, one parallel to flow direction and one perpendicular, conclusions drawn from the force term comparison are used to model limiting cases, which are interpreted as transition points for gravity independence. Experimental results for vertical upflow, vertical downflow, and horizontal flow condensation heat transfer coefficients are presented, and show that, for the given test section, mass velocities above 425 kg/m 2 s ensure gravity independent heat transfer. Parametric evaluation of the criteria using different assumed values of mass velocity, orientation, local acceleration, and exit quality show that the criteria obey physically verifiable trends in line with those exhibited by the experimental results. As an extension, the separated flow model is utilized to provide a more sophisticated approach to determining whether a given configuration will perform independent of gravity. Results from the model show good qualitative agreement with experimental results. Additionally, analysis of trends indicate use of the separated flow model captures physics missed by simpler approaches, demonstrating that use of the separated flow model with the gravity independence criteria constitute a powerful predictive tool for engineers concerned with ensuring gravity independent flow condensation heat transfer performance.